Promising Accurate Equation of State Models for High-Pressure, High-Temperature Wells - Babalola, Faith; Olasesan, Ibukunoluwa (Journal of Earth Energy Science, Engineering, and Technology, 2024)
This study analyzed and compared promising Equation of State models for High-Pressure High-Temperature (HPHT) well applications. The study examined four fluid phase behavior Equation of State (EOS) models namely, (Peng-Robinson (PR), Cubic-Plus-Association (CPA), Perturbed-Chain Statistical Associating Fluid Theory (PC-SAFT) and Peng-Robinson-Babalola-Susu (PRBS). Their strengths, weaknesses, and computational efficiencies in calculating molar volumes with pressure change were rigorously analyzed using the Python program for five reservoir fluid systems: WELL 1, WELL 2, WELL 3, WELL 4 and WELL 5. PRBS, PC-SAFT, and CPA showed accurate predictions at specific high-pressure ranges between 90 and 160 MPa on the average, PRBS exhibited the lowest percentage Absolute Average Deviation (%AAD) of 21.0, followed by PC-SAFT with 28.0, followed closely by CPA with 31.8 while PR was shown to be totally unapplicable to high pressure reservoir systems as it had a %AAD of 125.4.